Anger, agency, risk and action: a neurobehavioral model with proof-of-concept in healthy young adults - White, Tara L.; Gonsalves, Meghan A.; Zimmerman, Chloe; Joyce, Hannah; Cohen, Ronald A.; Clark, Uraina S.; Sweet, Lawrence H.; Lejuez, Carl W.; Nitenson, Adam Z. (Frontiers in Psychology, 2023)
Anger can engender action by individuals and groups. It is thus important to understand anger’s behavioral phenotypes and their underlying neural substrates. Here we introduce a construct we term agentic anger, a state that motivates action to achieve risky goals. We test predictions of our neurobehavioral model in two proof-of-concept studies. Study 1 used the Incentive Balloon Analogue Risk Task (iBART) in a within-subjects, repeated measures design in 39 healthy volunteers to evaluate: a) impact of frustrative non-reward on agentic anger, assessed by self-reports of negative activation (NA), b) impact of achieved reward on exuberance, assessed by self-reports of positive activation (PA), c) their interrelationship, and d) their relationship with traits of positive emotion, negative emotion, immersive emotion and impulsivity. Task-induced NA was positively correlated with task-induced PA (r=0.56, p<.001), risk-taking on the task (r=0.27 to 0.36, p≤.05, .01) and trait Social Potency (SP, r=0.34 to 0.35, p<.05), a measure of reward sensitivity on the Multidimensional Personality Questionnaire Brief-Form (MPQ-BF). Study 2 assessed functional MRI response to stakes for risk-taking in healthy volunteers receiving 20 mg d-amphetamine (AMP) in a double-blinded, placebo-controlled crossover design (N = 10 males; 20 MRI scans), providing preliminary information on ventral striatal response to risky rewards during catecholamine (CA) activation. Trait SP and task-induced PA were strongly positively related to AMP-facilitated BOLD response in the right nucleus accumbens, a brain region in which DA prediction error signal shapes action value and selection (SP r=+.60, p=.03; PA r=+.72, p=.02, respectively). Participants’ task-induced NA was also strongly positively related with trait SP (r=0.51; d=1.2) and task-induced PA (r=0.68; d=1.9), replicating the findings of Study 1. Together these results inform the phenomenology and neurobiology of agentic anger, which recruits incentive motivational circuitry and motivates personal action in response to goals that entail risk (defined as exposure to uncertainty, obstacles, potential harm, loss and/or financial, emotional, bodily or moral peril). Neural mechanisms of agency, anger, exuberance and risk-taking are discussed, with implications for personal and group action, decision-making, social justice, and behavior change.